ANALISIS PENGARUH CAR, LDR, NPL, BOPO, DAN SIZE TERHADAP ROA (Studi pada Bank Umum Konvensional yang Terdaftar di Bursa Efek Indonesia Periode 2010-2015) - Vernanda, Shinta Dewi; Widyarti, Endang Tri (Diponegoro Journal of Management, 2016)
This study aims to examine the effect of Capital Adequacy Ratio (CAR),Â  Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Operating Expenses Operating Income (BOPO), and Company Size (Size) on profitability of conventional commercial banks in Indonesia which proxied by Return On Assets (ROA).The population in this study is the commercial bank that listed in the Indonesia Stock Exchange (IDX) since 2010 until 2015. This research use purposive sampling with the following criteria: a bank has complete published reports in 2010-2015 and hasnâ€™t negative ROA. The samples in this study were 25 commercial banks. This study uses data obtained from Annual Financial Report issued by banks in the Publication Financial Statements Financial Services Authority (FSA). The analysis technique used is multiple linear regression analysis. Before using multiple linear regression analysis, performed classical assumption first.From the results of simultaneous hypothesis test (F test) showed that the CAR, LDR, NPL, BOPO, and Size had a significant effect on ROA with a significance level of 0.000. While based on the partial hypothesis test (t test) showed that the CAR had significant positive effect on ROA, BOPO had significant negative effect on ROA, while the LDR, NPL and Size had no significant effect on ROA. The results showed that variable BOPO had the biggest effect on ROA. The result of the degree of determination (Adjusted R Square) in the regression model is equal to 0.783. This shows that the effect of the independent variables, namely CAR, LDR, NPL, BOPO and Size to the dependent variable (ROA) is 78.3% while the remaining 21.7% is effected by other factors which were not explained in this research.